What is money? : bartering, cash, cryptocurrency ... and much more! - Green, Alicia (New York, NY : Children's Press, an imprint of Scholastic, Inc., 2024)
"A series to build strong financial habits early on in life! How can I make money? What is inflation? What is the difference between a debit card and a credit card? Economics - and more specifically, money - play such a large role in our lives. Yet there are many mysteries and misconceptions surrounding the basic concepts of finance and smart money management. This A True Book series offers students the know-how they'll need to start on the road to financial literacy - a crucial skill for today's world. Interesting information is presented in a fun, friendly way - and in the simplest terms possible - which will enable students to build strong financial habits early on in life. Understanding how society progressed from the barter system to currency - and how that money works in the global economy - are just two critical financial literacy skills that all kids should have. Did you know that the first paper currency appeared more than 1,200 years ago? Or that the currency of the future will likely be digital? Learn all this and more in What Is Money? - a book that starts kids on the road to financial literacy"--Provided by publisher.
Introduction -- The barter system: What did people do before money existed? -- Early forms of currency: What was commodity money and how did it work? -- Coins and paper money: How did money changed over time? -- The big truth: what makes money... money? : All paper currency shares unique features -- Money today: How does currency continue to evolve? -- Think like an economist -- Activity -- True statistics.
Includes bibliographical references and index.
Ages 8-10.
Grades 4-6.
Keywords: Money -- History -- Juvenile literature; Barter -- Juvenile literature; Paper money -- Juvenile literature; Cryptocurrencies -- Juvenile literature; JUVENILE NONFICTION / Concepts / Money; JUVENILE NONFICTION / General